Carbon Nanomaterials for Therapy, Diagnosis, and Biosensing - Mazzaglia, Antonino; Piperno, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In the landscape of the design of carbon nanomaterials, the fine-tuning of their functionalities and physico-chemical properties has increased their potential for therapeutic, diagnostic, and biosensing applications. In this editorial, we will provide a brief overview of the contents of this Special Issue. In particular, nanoplatforms originating from the synergistic combination of carbon-based nanomaterials (i.e., nanotubes, graphene, graphene oxide, carbon quantum dots, nanodiamond, etc.) with various functional molecules such as drugs, natural compounds, biomolecules, polymers, metal nanoparticles, and macrocycles that have useful applications in drug delivery, multi-targeted therapies, theranostic as well as scaffolds in tissue engineering, and as sensing materials have been selected for publication as Articles or Mini Reviews. The variety of applications covered by the nine articles published in this Special Issue of Nanomaterials are proof of the growing attention that the use of carbon nanomaterials in the biomedical/pharmaceutical field has received in recent years. We hope that readers find the contents of this Special Issue useful for their research, which is aimed to advance carbon nanomaterials from the laboratory to clinical nanomedicine.